Acceptance of mobile payments and UPI technology - Indian context. (5th December 2019) - Pillai, Sruthy S.; Sandhya, G.; Rejikumar, G.
The trend shows that more people prefer using the non-cash modes when cash shortage was at its crest even for small transaction. The context paved way for the researchers to examine consumer. We deployed the technology acceptance model (TAM) as the base theoretical framework to investigate into the subject matter. The premise for adopting the technology acceptance model is to measure and analyse the behaviour and attitude of customers towards adopting of mobile payment and UPI technology for transactions. The results suggested that there is a significant positive influence of simplicity and interoperability on the mobile payment adoption, timely contacts and security proved to have a negative influence on the dependent variable. People are more concerned about the security aspects as they believe that their monetary details are not safe while doing online transactions.